2016
DOI: 10.1021/acs.jpcc.6b06604
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Fused-Ring Thiophene Organic Dye-Sensitized Solar Cells

Abstract: Fused-ring thiophene compounds emerged as an important type of building blocks for organic dyes toward the dye-sensitized solar cells (DSSCs) because of their good charge transfer and light-harvesting properties. Nevertheless, some fused-ring thiophenes have a lack of desired alkyl chains or side alkyl chains, which may induce a severe charge recombination in devices. In this work, the hex-1-en-1-ylbenzene (HEYB) unit was introduced in two new fused-ring thiophene organic dyes (M60 and M59), resulting in a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…[27][28][29] DTP is accessible with a yield in one step up to 80%, and the N-position provides great opportunity for the control of dye aggregation, which makes it good for DSSC applications. As reported in our previous study, 30 DTP can be easily modied by the introduction of long-chain alkyl groups on the bridging nitrogen, and DSSCs fabricated by these DTP-based dyes achieved a PCE of 8.14%. Wang and co-workers reported a series of arylamine organic dyes bearing N-heterocycle-substituted DTP spacers displayed a PCE of 8.20%.…”
Section: Introductionsupporting
confidence: 66%
“…[27][28][29] DTP is accessible with a yield in one step up to 80%, and the N-position provides great opportunity for the control of dye aggregation, which makes it good for DSSC applications. As reported in our previous study, 30 DTP can be easily modied by the introduction of long-chain alkyl groups on the bridging nitrogen, and DSSCs fabricated by these DTP-based dyes achieved a PCE of 8.14%. Wang and co-workers reported a series of arylamine organic dyes bearing N-heterocycle-substituted DTP spacers displayed a PCE of 8.20%.…”
Section: Introductionsupporting
confidence: 66%
“…44,45 Dye TTZ11 was instead endowed with a dithieno[3,2-b:2 0 ,3 0 -d] pyrrole (DTP) moiety; in this case a better p-conjugation was expected due to the coplanar bridged p-system, which could possibly lead to an extension of the light absorption range of the sensitizer. [46][47][48] Finally, compound TTZ12 presented both the BTD and the DTP groups on the same molecular scaffold, a combination that was shown to enhance photovoltaic performances compared to dyes presenting the DTP unit alone. 49…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, most of these works focus on symmetric FTPs, FTPs with an asymmetric structure are rarely exploited, mainly owing to their great challenge of synthesis . Moreover, in our recent work, we proposed that a twisted structure is indispensable for reducing the charge recombination in FTPs based organic dye-sensitized solar cells . Studies revealed that at least 1% PCE improvement can be achieved by introducing the hexyl group in the center of organic dyes without bulky donors.…”
mentioning
confidence: 99%